The Relationship between Handwashing Behavior with Soap and the Incidence of Diarrhea in Children at Bojongsari 02 Elementary School, Bekasi Regency in 2024 - Resmawati, Resmawati; Mulyati, Rini; Ismafiaty, Ismafiaty (Jurnal KESANS : Kesehatan dan Sains, 2025)
Introduction: According to the World Health Organization 2024 diarrhea is the third leading cause of death in children. It is estimated that around 443,823 people die each year. Diarrhea is related to Clean and Healthy Living Behavior, environmental sanitation quality and unhygienic habits such as not washing hands before eating or after doing activities related to the environment. Objective: This study aims to determine the relationship between handwashing behavior with soap and the incidence of diarrhea in children at Bojongsari 02 Elementary School, Bekasi Regency. Method: The research design used an analytical survey design with a cross-sectional time approach. Data were analyzed using univariate frequency distribution analysis and bivariate chi-square data analysis with a significance of a = 0.05. Result and Discussion: The results of the study showed that there was a significant relationship between handwashing behavior with soap and the incidence of diarrhea in children at Bojongsari 02 Elementary School, Bekasi Regency (p-value 0.000). It was found that 56.1% of children at SDN Bojongsari 02, Bekasi Regency had adequate handwashing behavior with soap and 75.6% of children at Bojongsari 02 Elementary School, Bekasi Regency did not experience diarrhea in the last 3 months. Conclusion: It is recommended that nurse provide education or counseling on handwashing with soap (CTPS) in every elementary school in their work area.